Electronic information and educational environment as a condition for the implementation of English language programs in a maritime university - Regina Vladislavovna Drazhan (Вестник Майкопского государственного технологического университета, 2023)
The relevance of the research topic is determined by the need to reconsider the prospects for the language training of seafarers in the context of a pandemic and related socio-economic changes in the state and in the world, including the employment of seafarers, the competitiveness of graduates of Russian maritime universities, wages, etc. Effective communication in English has always been of great importance for the safe operation of ships and protection of the marine environment from shipping.The research problem is how does the electronic information and educational environment contribute to the successful implementation of English language programs and improve the quality of language training at a maritime university?The purpose of the research is to substantiate the effectiveness of the implementation of English language programs at the EIEE of the Institute.The research methods used are analysis, synthesis, generalization. The Institute ofWater Transport named after G.Ya. Sedov was the experimental basis of the research.The results of the research are the following: the English language programs implemented by the Institute have been described (goals, objectives, benefits, competencies being formed, form of organization and training mode); the forms of interaction between participants in the educational process at the EIEE of the Institute in the process of implementing English language programs have been disclosed; further prospects for the implementation of English language programs have been presented.Key conclusions: the electronic information and educational environment created at the Institute has proved the effectiveness of the implementation of English language programs, based on cooperation, consultation, and dialogue between participants in the educational process, including employers, which contributes to the development of teamwork skills and constructive resolution of problem situations.